Internalization of Smart Service Management in Improving Service Quality: The Case of Regional Library - Masruroh, Nikmatul; Sari, Rini Fatika; Novitasari, Indri Dwi Putri; Rini, Anggi Amanda Septia (Faculty of Economics and Business, Universitas Klabat, 2024)
Service quality is the main goal in providing satisfaction for the public. Especially services from regional institutions, in this case from Jember Regional Library which since the last 3 years has implemented digitalization in its services. So the purpose of this research, firstly; to explore the quality of services carried out by the Jember Regional Library, second; to explore smart services carried out by the Jember Regional Library, third; to analyze the process of internalizing smart service management in improving service quality at the Jember Regional Library. In achieving these objectives, this research uses a qualitative approach, descriptive type. The technique of determining research subjects with purposive technique. Data collection by observation, interview and documentation. This research results in first, the quality of library services has improved in quality and efficiency after digital transformation, second, the form of smart service in the library in the form of smart library is a new innovation by utilizing digital transformation in the service process. Third; smart service is internalized in the form of management that is managed from planning to evaluation and becomes a reference in service.